1991
DOI: 10.1111/j.1365-2621.1991.tb01158.x
|View full text |Cite
|
Sign up to set email alerts
|

The response of unripe Conference pears to modified atmosphere retail packaging

Abstract: Unripe green Conference pears with initial firmness values of 46-55N were sealed in modified atmosphere (MA) low density polyethylene (LDPE, 30 p) pillow packs and in perforated control packs on three dates during [1985][1986]. Changes in pack atmosphere composition, skin chlorophyll content, flesh firmness and sensory quality were monitored during 14-20 days simulated shelf-life at 20°C. In MA packs, equilibrated atmospheres containing 5-9% C02 and <5% 0 2 developed within c. 3 days. Chlorophyll degradation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…These results show that MA packaging retarded the rates of degreening and softening of conditioned, part-ripe Comice in much the same way as had been reported for unripe Conference (Geeson et al, 1991) and Comice pears. However, because the skin colour had already progressed to an acceptable stage of yellow before packing, the slight retardation in the rate of softening (Tables 3 and 4) in the one m-p MA packs appeared to offer a better opportunity for extending ambient shelf-life by several days without adversely affecting their eating quality, providing that the pears were not too soft when packed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results show that MA packaging retarded the rates of degreening and softening of conditioned, part-ripe Comice in much the same way as had been reported for unripe Conference (Geeson et al, 1991) and Comice pears. However, because the skin colour had already progressed to an acceptable stage of yellow before packing, the slight retardation in the rate of softening (Tables 3 and 4) in the one m-p MA packs appeared to offer a better opportunity for extending ambient shelf-life by several days without adversely affecting their eating quality, providing that the pears were not too soft when packed.…”
Section: Discussionsupporting
confidence: 81%
“…Previous work (Geeson et al, 1991) showed that, when unripe Conference pears (eight-fruit units) were held at 20°C in 30 p low density polyethylene (LDPE) modified atmosphere (MA) packs in which the atmosphere equilibrated to 5-9% C 0 2 and 2-5% 02, chlorophyll degradation was inhibited but flesh softening was only partly retarded. Moreover, pears held in MA packs failed to develop the normal sweet aromatic flavour and juicy, melting texture of normal 'eating-ripe' fruit, even when the packs were perforated to allow ingress of air after only 4 days at 20°C.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers (Smith et al. 1989; Geeson et al. 1991a,b) indicated similar color changes with pears from MAP.…”
Section: Resultsmentioning
confidence: 68%
“…The influence of MAP on quality of fruit with a naturally longer shelf life is variable. Some investigators report benefits on quality (firmness retention, reduced physiological disorders) in fruits with extended shelf life (Hewett and Thompson 1988; Geeson et al. 1991a; Zoffoli et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation